THE INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS CURRENT ISSUES AND SOLUTIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In the modern world, digital technologies have penetrated into all spheres of society and are radically changing them. The introduction of innovative technologies into the educational process is one of the most pressing problems today. The article discusses the introduction of innovative technologies in education, their advantages and problems.